Gambaran Potensi Interaksi Obat Metformin pada Pasien Diabetes Melitus Tipe 2 di Instalasi Rawat Jalan RS Nur Hidayah - Puji Lestari, Mardiana (Sahabat Publikasi Kuu, 2024)
Background: Diabetes mellitus (DM) is a metabolic disorder caused by damage or inability of pancreatic β cells to produce insulin. Type 2 DM patients are often accompanied by accompanying diseases that are either a complication of type 2 DM or the presence of other diseases so that the drugs used will be more. More drugs taken at the same time can increase the risk of unwanted drug interactions. Research Objectives: This study aims to evaluate the potential interaction of metformin with other drugs in patients with type 2 DM on the road at Nur Hidayah Bantul Yogyakarta Hospital. Research Methods: Descriptive observational research with retrospective data collection. The data collection technique used purposive sampling method. Samples that met the inclusion criteria were obtained as many as 82 patients. Data analysis used univariate analysis to describe patient characteristics and treatment, as well as identification of drug interactions based on Drugs.com. Research Results: In this study, the majority of patients with type 2 DM were aged 61-80 years 47.6%, female 63.4% and had comorbidities 89.0%. Treatment of type 2 DM patients mostly used combination therapy regimens as much as 78% of combinations, with a combination of 2 drugs, namely metformin and glimepiride 35.4%, getting ≥5 drugs 59.8%. Potential drug interactions of metformin with other drugs as much as 85.4% experienced drug interactions with moderate severity 88.6% and the most common drug interactions were metformin and glimepiride 37.1%. Conclusion: The majority of type 2 DM patients in the outpatient installation of Nur Hidayah Bantul Yogyakarta Hospital experienced potential metformin drug interactions.